Developing an Educational Design Pattern Language for MOOCs - Fassbinder, Aracele Garcia de Oliveira; Barbosa, Ellen Francine; Magoulas, George D. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2017)
The paper advocates a course design approach based on learning design patterns and introduces a pattern language to support design for learning in Massive Open Online Courses (MOOCs). The current version of the Educational Design Pattern Language contains thirty-nine patterns organized into eight categories. Furthermore, it is guided by the Flipped Learning Teaching Model as a pedagogical approach. The paper discusses theoretical and practical aspects of the pattern language, its development, validation, and usefulness for educators and technologists. The application of the approach is illustrated with a case study in the area of Software Engineering education.